2019
DOI: 10.1136/heartjnl-2018-314512
|View full text |Cite
|
Sign up to set email alerts
|

Comparative trends in coronary heart disease subgroup hospitalisation rates in England and Australia

Abstract: BackgroundPopulation-based coronary heart disease (CHD) studies have focused on myocardial infarction (MI) with limited data on trends across the spectrum of CHD. We investigated trends in hospitalisation rates for acute and chronic CHD subgroups in England and Australia from 1996 to 2013.MethodsCHD hospitalisations for individuals aged 35–84 years were identified from electronic hospital data from 1996 to 2013 for England and Australia and from the Oxford Region and Western Australia. CHD subgroups identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
3
18
0
1
Order By: Relevance
“…1 2 In England, too, these latter downward trends have been seen for deaths from CHD, 2 3 and specifically from MI. 4 5 Despite this, CHD remains a major cause of morbidity, 6 and it costs England's National Health Service (NHS) over £950 million per year. 2 Hospital admission rates for MI are an important measure of CHD burden in the population, but have generally been reported in studies covering relatively short time periods.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 In England, too, these latter downward trends have been seen for deaths from CHD, 2 3 and specifically from MI. 4 5 Despite this, CHD remains a major cause of morbidity, 6 and it costs England's National Health Service (NHS) over £950 million per year. 2 Hospital admission rates for MI are an important measure of CHD burden in the population, but have generally been reported in studies covering relatively short time periods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from some western countries showed that the adjusted incidence trend of IHD or MI decreased over the same time period. 20,22 A binational study of more than 7 million IHD hospitalizations in England and Australia highlighted that the age-adjusted hospitalization rates for total IHD declined in Australia from 1996 to 2013 (with an average annual percent change of −3.0); meanwhile, IHD 25 Previous studies showed that the trends of agestandardized IHD mortality declined in high-income western regions from 1980 to 2010, but they increased in South Asia, Central Asia, East Asia, and Eastern Europe.…”
Section: Discussionmentioning
confidence: 99%
“…17 In CD-ICD-10 method, subgroups of IHD included myocardial infarction (MI) (I21 and I22), unstable angina (I20.0), stable angina (I20.1-I20.9), and other IHD such as chronic IHD (I25), other acute IHD (I24), and complications following acute MI (I23). 20 IHD patients were identified based on primary diagnoses or underlying causes of death and the secondary diagnoses at discharge from hospital or contributory causes of death from death certificate. In WHO-MONICA method, events are classified as firstever or recurrent and fatal or non-fatal.…”
Section: Data Collectionmentioning
confidence: 99%
“…Comprehensive Big Data systems will allow studies of whole populations over many decades to be performed in a timelyand cost-effective manner. Whole-of-population coverage importantly provides the power to identify even marginal shifts in outcomes as a result of new policies or interventions, to detect changes in population groups where numbers of cardiovascular events are relatively low but rising (such as in younger women [23]), and for long-term follow-up along the life course, with better opportunities for inferring cause, with adjustment for confounders. Population-based data provide complete coverage of communities, ensuring inclusiveness and generalisability of results.…”
Section: Population Health and Outcomes Researchmentioning
confidence: 99%